2011
DOI: 10.1002/jor.22029
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells in synovial fluid increase in the knee with degenerated cartilage and osteoarthritis

Abstract: We investigated whether mesenchymal stem cells (MSCs) in synovial fluid (SF) increased in the knee with degenerated cartilage and osteoarthritis. SF was obtained from the knee joints of 22 patients with anterior cruciate ligament (ACL) injury during ACL reconstruction, and cartilage degeneration was evaluated arthroscopically. SF was also obtained from the knee joints of 6 healthy volunteers, 20 patients with mild osteoarthritis, and 26 patients with severe osteoarthritis, in which the grading was evaluated ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
174
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 34 publications
12
174
1
8
Order By: Relevance
“…Surprisingly, donor age had no signficiant effect on initial CFU concentrations or cell proliferation. The cell populations expanded in monolayer culture expressed osteogenic, adipogenic and chondrogenic phenotypes under standard in vitro culture conditions, consistent with findings in similar studies [4,5,10,12], and reflecting the multi-lineage potential requirement for MSCs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Surprisingly, donor age had no signficiant effect on initial CFU concentrations or cell proliferation. The cell populations expanded in monolayer culture expressed osteogenic, adipogenic and chondrogenic phenotypes under standard in vitro culture conditions, consistent with findings in similar studies [4,5,10,12], and reflecting the multi-lineage potential requirement for MSCs.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of MSCs in synovial fluids was first reported in 2004 [8], and subsequent studies have corroborated this finding in several model species, including the horse [9][10][11][12]. The proliferative and differentiation capacities of synovial fluidderived progenitor cells have varied between studies [9][10][11][12][13], but in all cases, these cells were capable of chondrogenesis.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…4 In OA, our lab and others have shown that sfMPCs have increased proliferative but reduced chondrogenic capacities. 5,6 OA is a multifaceted disease and many factors may contribute to the change in phenotype between normal and OA sfMPCs. The synovial environment changes physically, chemically, and physiologically with injury or the onset of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Trabecular bone MSCs sorted on the basis of CD271 expression revealed that OA MSCs exhibit an age-related proliferation deficiency in vitro [69]. In OA patients, the number of MSCs in the synovial fluid compartment is much greater than in samples from healthy joints, and the number of cells increased with the severity of OA progression [70]. Synovial fluid MSCs show greater chondrogenic capability than MSCs separated from bone marrow [71].…”
Section: Atypical Activity Of Mscs In Oamentioning
confidence: 99%